2015
DOI: 10.1021/acsnano.5b05792
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Synthesis of Hybrid Nanoparticles with Controlled Lipid Layers: Understanding Flexibility-Regulated Cell–Nanoparticle Interaction

Abstract: The functionalized lipid shell of hybrid nanoparticles plays an important role for improving their biocompatibility and in vivo stability. Yet few efforts have been made to critically examine the shell structure of nanoparticles and its effect on cell-particle interaction. Here we develop a microfluidic chip allowing for the synthesis of structurally well-defined lipid-polymer nanoparticles of the same sizes, but covered with either lipid-monolayer-shell (MPs, monolayer nanoparticles) or lipid-bilayer-shell (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
123
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 42 publications
(83 reference statements)
8
123
0
2
Order By: Relevance
“…More importantly, their shell rigidity was controlled to regulate the cellular uptake. Sun et al prepared LPNs having structures of PLGA-lipid and PLGA-water-lipid (by altering the injection order of the PLGA and lipid-PEG organic solutions in the microfluidic chips) which had Young's modulus of 1.2 and 0.76 GPa, respectively (Sun et al, 2015). They found that the more rigid NPs had a much higher cellular uptake than the less rigid ones.…”
Section: Hybrid Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, their shell rigidity was controlled to regulate the cellular uptake. Sun et al prepared LPNs having structures of PLGA-lipid and PLGA-water-lipid (by altering the injection order of the PLGA and lipid-PEG organic solutions in the microfluidic chips) which had Young's modulus of 1.2 and 0.76 GPa, respectively (Sun et al, 2015). They found that the more rigid NPs had a much higher cellular uptake than the less rigid ones.…”
Section: Hybrid Nanoparticlesmentioning
confidence: 99%
“…Copyright (2010) American Chemical Society. (Sun et al, 2015) 28 † High throughput: ≥1 g/h; low throughput: < 1 g/h. Abbreviation: PLGA, poly(lactic-co-glycolic acid); DSPE-PEG, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxy(polyethylene glycol); DPPC, dipalmitoylsn-glycero-3-phosphocholine; NIPA, N-isopropylacrylamide; DCP, dihexadecyl phosphate; EPC, L-α-phosphatidylcholine (egg PC); n/a, not available.…”
Section: Hybrid Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the lipid system is undoubtedly one of the most popular nonviral vehicles for gene delivery. [11][12][13][14][15][16][17] The lipid bilayer can protect nucleic acids from degradation and enable efficient endosomal escape. 18,19 However, the present lipid systems, such as Lipofectamine 3000, are still not competent to deliver CRISPR/Cas9 because of their relatively low transfection efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Microparticles have been extensively studied as delivery vehicles of proteins, peptides, and some small molecule drugs [1][2][3][4][5][6]. Compared with conventional forms of drug delivery via long-term frequent oral intake or injections to maintain a constant drug concentration, microparticle-based delivery systems can control both the level of the drugs and their lifetime in the body, and improve pharmacokinetics by sustained release of the drugs.…”
Section: Introductionmentioning
confidence: 99%